Antibody to herpes simplex virus type 2 as a marker of sexual risk behavior in rural Tanzania. - Obasi, A; Mosha, F; Quigley, M; Sekirassa, Z; Gibbs, T; Munguti, K; Todd, J; Grosskurth, H; Mayaud, P; Changalucha, J; Brown, D; Mabey, D; et al. (1999)
A serosurvey was conducted in a random sample of 259 women and 231 men in 12 rural communities in Mwanza Region, Tanzania, using a type-specific ELISA for Herpes simplex virus type 2 (HSV-2) infection. Seroprevalence rose steeply with age to approximately 75% in women >=25 years old and 60% in men >=30. After adjusting for age and residence, HSV-2 prevalence was higher in women who were married, in a polygamous marriage, Treponema pallidum hemagglutination assay (TPHA)-positive, had more lifetime sex partners, or who had not traveled. Prevalence was higher in men who were married, had lived elsewhere, had more lifetime partners, had used condoms, or were TPHA-positive. HSV-2 infection was significantly associated with recent history of genital ulcer. The association between HSV-2 infection and lifetime sex partners was strongest in those <25 years old in both sexes. This association supports the use of HSV-2 serology as a marker of risk behavior in this population, particularly among young people.